PEMBERDAYAAN MASYARAKAT LOKAL MELALUI PROGRAM CORPORATE SOCIAL RESPONSIBILTY (CSR) PADA PT. PIR KECAMATAN PERANAP KABUPATEN INDRAGIRI HULU - Resta Irmia; Ernawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Corporate Social Responsibility (CSR) is a concept or action taken by the company as a sense of corporate responsibility towards the social and the environment around the company is located. The company that is the object of the author's research is PT. Development of Investment Responsibility (PIR) of Indragiri Hulu District, Peranap District. Which local communities have not felt the benefits of the existence of PT. Increased Investment in Riau (PIR) in their area, namely Peranap District, Indragiri Hulu Regency. The purpose of this study is to find out how to empower local communities through corporate social responsibility (CSR) programs. At PT. Riau Investment Increase (PIR) in the role of the upstream Indragiri district. The theory used in this research is CSR Implementation theory according to Untung, namely: Accountability, Openness, Fairness, The responsibility of this research method uses a qualitative approach with a purposive sampling technique by interview (interview) , observation (direct observation), study of literature and documentation as a source of information and data analysis. The results of this study found that the empowerment of Indigenous Peoples Empowerment through the Corporate Social Responsibility (CSR) Program has not been implemented optimally. Inhibiting Factors in Empowering Indigenous Peoples Through Corporate Social Responsibility (CSR) Programs at PT. Riau Investment Development is the lack of a relationship approach between the company and the community so that the distribution of aid does not match what is needed by the community, the lack of quality human resources of the local community so that it cannot recruit in large numbers from the local community, and the lack of response from the community can be concluded that the program empowerment of local communities through CSR has not yet been carried out to the maximum. Keywords:  Empowerment of Local Communities, Corporate Social Responsibility